DEVELOPING ELT MATERIALS-ICT BASED AMID COVID-19 - Muthmainnah Muthmainnah; Riswanto Riswanto; Santiana Santiana; Eka Apriani; Syafryadin Syafryadin; Nurul Fadhillah (University of Kuningan, 2022)
This study investigates the analysis of the needs of EFL students in using ICT as an ELT tool and material. This quantitative study involved 162 students drawn from twelve study programs: department of mathematics, department of Indonesian language, department of agriculture, department of agrotechnology, department of agribusiness, department of informatics engineering, department of information systems, department of communication Science, Department of Communication Science, department of State administration, department of health and society, department of Islamic economics at Universitas Al Asyariah Mandar. In this study, we will see how the development of modern information and communication technology (ICT) as tools and materials used in the classroom to help students learn English 1. Therefore, the purpose of this research is to examine what the needs and wants are and their shortcomings. Data has been collected and analyzed using a hybrid approach with questionnaires and interviews. This study found that most of the participants found it useful to integrate social media such as Youtube based as material, WhatsApp to communicate, and they recommended maximizing the use of Google technology (e-dictionary), Duolingo application, Rosetta Stone, Daily Learn English, and ELT in a virtual classroom in the middle COVID-19. Students were selected using a selective random sampling technique. The findings reveal that the genre approach media and technology is used to developing ICT as an English foreign language resource in higher education teaching are recommended by the findings of this study.